Induced cortical tension restores functional junctions in adhesion-defective carcinoma cells. Issue 1 (December 2017) - Ito, Shoko; Okuda, Satoru; Abe, Masako; Fujimoto, Mari; Onuki, Tetsuo; Nishimura, Tamako; Takeichi, Masatoshi
Abstract Normal epithelial cells are stably connected to each other via the apical junctional complex (AJC). AJCs, however, tend to be disrupted during tumor progression, and this process is implicated in cancer dissemination. Here, using colon carcinoma cells that fail to form AJCs, we investigated molecular defects behind this failure through a search for chemical compounds that could restore AJCs, and found that microtubule-polymerization inhibitors (MTIs) were effective. MTIs activated GEF-H1/RhoA signaling, causing actomyosin contraction at the apical cortex. This contraction transmitted force to the cadherin-catenin complex, resulting in a mechanosensitive recruitment of vinculin to cell junctions. This process, in turn, recruited PDZ-RhoGEF to the junctions, leading to the RhoA/ROCK/LIM kinase/cofilin-dependent stabilization of the junctions. RhoGAP depletion mimicked these MTI-mediated processes. Cells that normally organize AJCs did not show such MTI/RhoA sensitivity. Thus, advanced carcinoma cells require elevated RhoA activity for establishing robust junctions, which triggers tension-sensitive reorganization of actin/adhesion regulators. Cancer cells can disrupt cell-to-cell junctions, thus allowing migration and metastasis. Here starting from a chemical screening, Ito et al. reconstitute a step-by-step mechanism linking microtubule depolymerization and epithelial cell junction restoration.